No friend of democracy : a study of Roman Catholic politics, their influence on the course of the present war and the gowth of Fascism - Moore, Edith (London : International Publishing Company, 1941)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 2; fascisme; Katholieke Kerk